Study of Momentum and Impulse by Setting NHT Cooperative Model with Worksheet Based RGM for Senior High School - Rayendra Wahyu Bachtiar, I Ketut Mahardika, Lika Indria Riswati, (International Journal of Scientific Research and Management (IJSRM), 2017)
This article studies on the momentum and impulse learning using NHT cooperative model with worksheet based RGM. This study aims to describe how to teach momentum and impulse using NHT cooperative models with worksheet based RGM. The data of study was collected trough descriptive method by describing data in the form of qualitative research studies that have been written by experts from variety sources. The sources of information are obtained by observation data, journals, text book, proceeding or scientific article. Data that has been obtained so will be analyzed as a classifying procces and collecting data. The result showed that momentum and impulse learning using NHT cooperative model with worksheet based RGM could make the learning process becomes more effective because the student participated directly on the learning process so they could improve their learning outcomes (cognitive and affective)